Quantum chemical study of the mechanism of the palladium-catalysed C−H acetoxylation of benzene. (February 2019) - Beyzaie, Nazanin; Tayyari, Sayyed Faramarz; Vakili, Mohammad; Beyramabadi, Safar Ali
In this work, the mechanism of the palladium-catalysed acetoxylation of benzene C-H has been studied theoretically in detail. Based on experimental studies, a four-step mechanism for this reaction had been proposed, that is, C−H activation of benzene is the rate-determining step which forms an intermediate ( k 1 pathway) which is subsequently oxidized to produce a high-valent Pd intermediate ( k 2 pathway). Using quantum chemical calculations, all pathways were investigated, and the activation energy, activation enthalpy and activation Gibbs free energy for all steps were calculated and compared with each other. It was determined that the RDS proceeds through a square complex instead of a T-shaped complex. The activation energy related to the k 2 pathway is higher than that of the RDS, and therefore, a new mechanism is proposed.